High Temperature‐Stable Perovskite Solar Cell Based on Low‐Cost Carbon Nanotube Hole Contact. Issue 17 (23rd February 2017) - Aitola, Kerttu; Domanski, Konrad; Correa‐Baena, Juan‐Pablo; Sveinbjörnsson, Kári; Saliba, Michael; Abate, Antonio; Grätzel, Michael; Kauppinen, Esko; Johansson, Erik M. J.; Tress, Wolfgang; Hagfeldt, Anders; Boschloo, Gerrit
Abstract : Mixed ion perovskite solar cells (PSC) are manufactured with a metal‐free hole contact based on press‐transferred single‐walled carbon nanotube (SWCNT) film infiltrated with 2, 2, 7, ‐7‐tetrakis(N, N‐di‐p‐methoxyphenylamine)‐9, 90‐spirobifluorene (Spiro‐OMeTAD). By means of maximum power point tracking, their stabilities are compared with those of standard PSCs employing spin‐coated Spiro‐OMeTAD and a thermally evaporated Au back contact, under full 1 sun illumination, at 60 °C, and in a N2 atmosphere. During the 140 h experiment, the solar cells with the Au electrode experience a dramatic, irreversible efficiency loss, rendering them effectively nonoperational, whereas the SWCNT‐contacted devices show only a small linear efficiency loss with an extrapolated lifetime of 580 h. Abstract : A perovskite solar cell with carbon nanotube‐based hole contact and drop cast 2, 2, 7, 7‐tetrakis( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 90‐spirobifluorene (Spiro‐OMeTAD) exhibits superior stability over the standard device with spin‐coated Spiro‐OMeTAD and evaporated gold contact. The solar cells are subjected to a 140 h maximum power point tracking stability experiment in 1 sun illumination and 60 °C, and the carbon‐based cell outperforms the gold cell clearly.